Pemanfaatan Sabut Kelapa Sebagai Inovasi Fake Nail - Agus Susanti; Tania Dewi Ariyanti (Garina, 2023)
Making fake nails using coconut coir is product that can beautify your appearance, reduce the accumulation of coconut coir waste and can be used as an opportunity for entrepreneurship. The purpose of this study is to find out and explain the process of making fake nails, product validation, and public acceptance of the Utilization of Coconut Coir as a Fake Nail Innovation. The methods used are observation, literature, experiments, documentation, interviews, and questionnaires. The process of making coconut coir fake nails goes through 3 stages, namely preparation of tools and materials, the process of making coconut coir fake nails, and attaching accessories to fake nails. There was evidence of product validation by 5 validators with the result that fake nails from coconut coir waste which had a reddish-brown color, smooth texture and very clear fiber motifs were the most chosen by the validators. The public test results in the average color category obtained 2.5 are very fond of (3). In the average texture category, 2.5 is very like (3) and for the pattern category, the average is 2.6, very like (3). A total of 3 average categories obtained, namely 2.545, are included in the very like category so that the product can be accepted by the community and can be used as a business opportunity. The advice given is another, faster technique for attaching coconut coir to fake nails.